Yankee go home, but take me with you: yet another perspective on Indo-American relations - Ramesh, Jairam (1999)
What India seeks in its relationship with the US is very simple - we want the US to be out but we want to be in with it. The last decade has seen India and America set aside the bitterness and hostility of the past and engage themselves in dialogue across a broad spectrum. This paper lays out the menu on some of the more prominent issues so that it is possible for us to identify what we like and what we dislike. - Reproduced
Keywords: India - Foreign relations - United States; International relations